Palm oil mill effluent as alternate carbon source for ammonia removal in wastewater treatment - Loh, Leh-Ming; Yan, Yi-Wei; Yap, Pui-Woon; Rupinee Nadarajan; Ong Soon-Hock, Augustine (Penerbit Universiti Kebangsaan Malaysia, 2019)
To address high demand in searching for carbon sources alternatives in ammonia wastewater treatment, comparison among various carbon sources in term of pollutants reduction efficiency was essential to determine the most cost-effective carbon source selection for industry scale in bulk amount. This study focuses on investigating palm oil mill effluent (POME) as the alternate carbon source for supporting ammonia oxidizing bacteria (AOB) in ammonia removal of glove industrial wastewater treatment. Ammonia reduction efficiency was compared between POME with molasses, one of the most commonly used carbon sources. POME as carbon source in ammonia wastewater treatment had shown significant comparable reduction efficiency as compared to molasses. Furthermore, the study on various mixture ratios of POME-molasses had also shown further improvement in ammonia reduction efficiency. At the optimum ratio of 50:50 (v/v) POME-molasses as carbon source mixture, the ammonia reduction in the treatment system had achieved 53.11% reduction, which reduced ammonia content down to 10.49 mg/L NH3. In this study, the results suggested that POME showing great potential to be the new cost-effective carbon source alternative in industry scale treatment.